Memory Transfer Language: an absolute learner-driven visualizer (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This article discusses visualization as a technique to enhance programming comprehension. It points out that current animation approach, being machine-based technique, is inadequate due to the fact that machine-based animation tools are difficult to integrate in the current teaching materials. In addition, machine-centered animators do not guarantee the learner with absolute engagement. In this paper, MTL, as a visualization technique which is absolutely learner-driven is demonstrated and discussed. It is shown that MTL can be integrated with current materials for teaching and learning programming and it can guarantee absolute authority to the learner.